Was Germany ever united? Borders and domestic trade, 1885 - 1933 - Nikolaus Wolf (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2006)
Was Germany ever united? Given the historical circumstances of Germany's unification in the 19th century there is no obvious answer to this question. But such an answer can affect the prospects of the post-1989 unification process, and beyond this of European integration. We provide an econometric analysis of Germany's economic integration across various internal borders from the foundation of the Kaiserreich until the end of the Weimar Republic. This analysis is based on a new comprehensive set of domestic trade flow data on railways and waterways, covering all parts of Germany 1885-1933. First, the disintegration effects by the separation of Alsace-Lorraine and Western Poland from Germany after the Versailles treaty were somewhat limited by previous disintegration of these regions. Second, while there is broad support for increasing integration across old political, administrative, and confessional borders between 1885 and 1933, a geographical divide between eastern and western parts of Germany had a persistent trade diverting effect well into the 1930s.
Keywords: F15; N13; N14; N90; 330; Germany; Economic Integration; Railways; Waterways